Centres for Health Evidence Demonstration Project - Stewart, Tracy; Koufogiannakis, Denise; Hayward, Robert S.A.; Crumley, Ellen; Moffatt, Michael E. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This paper will report on the establishment of the Centres for Health Evidence (CHE) Demonstration Project in both Edmonton at the University of Alberta and in Winnipeg at the University of Manitoba. The CHE Project brings together a variety of partners to support evidence-based practice using Internet-based desktops on hospital wards. There is a discussion of the CHE's cultural and political experiences. An overview of the research opportunities emanating from the CHE Project is presented as well as some early observations about information usage.